MAPPING INTEGRATIVE GREEN JOBS STRATEGIES IN TOURISM TVET CURRICULUM: A BIBLIOMETRIC ANALYSIS - Bimo Kuncoro Jati; Riswano; Rachmadina Rafika Triani; Kezia Elsty; Meisya Anggraini; Candra Karismawan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Sustainability has become a priority for the global tourism industry, requiring a workforce equipped with green skills. However, the integration of these competencies within Technical and Vocational Education and Training (TVET) remains fragmented. This study aims to map the scientific evolution of research regarding sustainable tourism competencies in vocational education. Using a bibliometric approach, data was retrieved from Google Scholar, then analyzed using VOSviewer and Biblioshiny. The results demonstrate a significant upward trend in publications from 2015 to 2025. Key research clusters center on "green skill," "green job," "hospitality," and "TVET college". Overlay visualization reveals a thematic shift from foundational concepts (2021–2022) toward specific implementation strategies and curriculum mapping (2023–2024). While TVET institutions are strategic facilitators for the green transition, current curricula often lack an integrative framework. These findings provide a roadmap for educators and policymakers to design competency-based programs that align vocational training with the demands of a circular economy